Evaluating Various Building Types for Optometry Tenants - Willerton, Dave; Grandfield, Jeff (Canadian Journal of Optometry, 2017)
Whether you are opening your first optometry clinic or considering moving your operations to another lo-cation, one of the first things to remember is that not all buildings and/or properties are created equally. Although the fundamentals of negotiating commercial leases are the same regardless of where you have your business [...]